THE INFLUENCE OF PLACEMENT ON EMPLOYEE PERFORMANCE IN THE GROGOT CLASS II STATE COURT OFFICE - Indah Indah; Farida Islamiah; Achmad Aprianor Firdaus (PIRSAP (Paser Institute for Scientific Research and Publications), 2023)
This research aims to assess the influence of the Placement variable (X) (Education, Work Knowledge, Work Skills and Work Experience) on Employee Performance (Y) at the Class II Tanah Grogot District Court Office. The sample consisted of 34 employees, selected using a saturated sampling technique. The questionnaire with 13 statements was tested for validity and reliability before multiple linear regression analysis using SPSS. The instrument test results show good validity and reliability. Regression equation: Y = 1.460 – 0.133 X1 + 0.398 X2 – 0.133 X3 + 0.551 X4. The correlation between the Placement variable and Employee Performance is strong (R = 0.762). The coefficient of determination (Adjusted R2) is 52.2%, the remainder is explained by other variables. The F test shows a significant effect simultaneously (Fcount > Ftable, p-value < α), rejecting H0. The t test shows that Job Knowledge (X2) and Work Experience (X4) have a significant effect on Employee Performance, while Education (X1) and Work Skills (X3) are not significant. The dominant variable is Job Knowledge (X2) with the highest t-count (3.198) and the lowest significant value (0.003). In conclusion, the Job Knowledge variable has the most significant influence on employee performance at the Class II Tanah Grogot District Court Office.